Enhancing Boiling and Explosive Breakup of Evaporating Heterogeneous Water Drops in High Temperature Gaseous Media; Chemical and Petroleum Engineering; Vol. 54, iss. 1-2 - Borisova A. G. Anastasiya Gennadjevna (2018, 2018)
Title screen